The Meaning of the Forming Elements of the Greeting 'Aisatsu' in Japanese - Asep Achmad Muhlisian; Yayat Hidayat (Chi'e: Journal of Japanese Learning and Teaching, 2023)
Greetings are categorized as an essential element in daily communication in Japan. The Japanese language learners besides learning the language must be able to culture as well. In this study, we discuss the meaning of the forming elements of the greeting "aisatsu" in the Japanese language which was analyzed using a qualitative descriptive method by taking data sources from Nihongo Nooryoku Shiken Shutsudai Kizun as many as 31 expressions related to everyday greetings equivalent to elementary and intermediate levels. The results of the study found that after going through the sorting process based on the basic word and affix and then also describing the lexical meaning of each expression, it can be seen that there is a relationship between the forming of the expression and the meaning of the expression after being used as a greeting and both these basic expressions influence each other in forming greeting expressions or aisatsu in Japanese. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalJapanese ExpressionJapanese AisatsuJapanese Studies